Control of urea volatilization loss by soluble salts and urease inhibitors - Khanif, Y. M.; Wong, L. P. (1987)
Ammonia volatilization loss from surface applied urea is a serious problem. Several chemicals, including soluble salts and urease inhibitors could be used to reduce this loss. In a laboratory study, Ca, K and Mg supplied as CaCl2, KCl. and MgS04 respectively and two urease inhibitors, phenylphosphorodiamidate (PPD) and hydroquinone were tested on Serdang series soil (Typic Paleudult). The rates of cations used were 0, 0.25, 0.5, 1.0 and 2.0 cation/N chemical equivalent ratio, while the rates of urease inhibitors were 0, 0.5, 1.0, 2.0 and 5.0% of the N app l.Le d . Urea-N at 400 ug/g was used and the soil mois ture was main tained at 30% (w/w). The volatilization loss was delenninecl directly by measuring the amount of ammont a evolved into Cl boric acid trap. Daily measurements were made up to seven days. Urea loss in the control ranged from 31 to 42%. All the treatments were effective in reducing urea loss. Ammonia loss was progressively less with increasing cation/N chemical equivalent ratios and also with Increasinq rate of urease inhibitors. For the Ca, K and MG tretments, the volatilization loss WaS effectively reduced at the rate of >0.5 cation/N chemical ecuivalent ratio. At the highnest rat e (2. 0 cation/N), the loss was 1esst than 13% • Tretments with the two inhibitors indicated that at the Lowest: rate of 0.5% the loss was reduced to half that of the control. Further increase in inhibitor rates did not markedly reduce the volatilization 1oss